2012
DOI: 10.1186/2047-783x-17-26
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of five equations for estimating resting energy expenditure in Chinese young, normal weight healthy adults

Abstract: BackgroundMost resting energy expenditure (REE) predictive equations for adults were derived from research conducted in western populations; whether they can also be used in Chinese young people is still unclear. Therefore, we conducted this study to determine the best REE predictive equation in Chinese normal weight young adults.MethodsForty-three (21 male, 22 female) healthy college students between the age of 18 and 25 years were recruited. REE was measured by the indirect calorimetry (IC) method. Harris-Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
34
2
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 42 publications
6
34
2
4
Order By: Relevance
“…Furthermore, the results confirm that population specific prediction equations with respect to ethnicity and body type are necessary [12–16, 2123]. …”
Section: Discussionsupporting
confidence: 65%
“…Furthermore, the results confirm that population specific prediction equations with respect to ethnicity and body type are necessary [12–16, 2123]. …”
Section: Discussionsupporting
confidence: 65%
“…Statistical analysis confirmed that the Mifflin equation is more suitable than the other equations for estimating RMR among obese diabetic patients. Similar findings were reported in many previous studies [8][9][10][11]30,31]. On the other hand, although differences between measured and predicted RMR in obese non-diabetic individuals is lowest for Mifflin equation, statistical analysis showed significant difference between the two methods.…”
Section: Discussionsupporting
confidence: 79%
“…These equations are simple, easy to use, and universally available. However, in spite of their extensive use, they have been found to be inaccurate in a variety of clinical settings [8,9]. While the Harris-Benedict equation had been used for estimating the basal metabolic rate, previous studies have found that it estimates RMR rather than basal metabolic rate, due to the test subjects not spending the night at the test facility [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many literature reports have compared predictive equations for specific populations to IC in order to determine the best equation for a given group [5][6][7] . Lopes et al 5 compared the Food and Agriculture Organization/World Health Organization/United Nations University, Harris and Benedict, Henry and Rees and Schofield equations in 30 subjects of both sexes with grade one obesity residing in the city of Porto Alegre (RS).…”
Section: Introductionmentioning
confidence: 99%